The Use of Information System Technology to Develop Tests on Insider Trading and Asymmetric Information - Marsden, James R.; Tung, Y. Alex (Management Science, 1999)
Issues related to insider trading remain popular research topics. Empirical studies using historical data are limited by two key factors: 1) the inability to identify exactly who possesses inside information, and 2) the inability to identify the accuracy of information possessed. Advances in information system technology enable us to overcome these problems in the laboratory. Using this technology, we create a research shell to conduct experiments where we can identify the exact type and quality of information accessible by each trader. Our system includes the capability to monitor individual activities in accessing inside information. The system can automatically impose a monetary penalty if random monitoring identifies a trader accessing inside information. Our experiments involve traders who receive access to inside information without initial knowledge of the quality of that information. The results indicate that traders were able to outperform the market if penalties for being caught accessing such information were not included. Once penalties were included, however, no significant performance differences were observed. Finally, in a second set of experiments involving a simplified market with infrequent electronic monitoring and low penalty amounts, inside information seemed to be rapidly and effectively disseminated to traders possessing no inside information.